Development and Evaluation of Fermented Semi-Dry Mutton Sausages during Storage at Ambient (29+10C) Temperature - B, Eswara Rao; P.R.S, Moorthy; K, Sudhakara Reddy (Journal of Meat Science, 2012)
In the this study, semi-dry fermented mutton sausages were developed by fermentation and drying technology by three different lactic acid bacteria viz., Lactobacillus casei, Lactobacillus plantarum and Pediococcus pentosaceus and storage studies were conducted for the semi- dry fermented mutton sausages in regular intervals at ambient (29+10C) temperature. The per cent moisture of semi-dry fermented mutton sausages as effected by lactic acid bacteria were significantly (P>0.01) lower whereas protein and fat were higher than control at room temperature storage. Among treatments lower per cent moisture and higher protein and fat were observed in sausages fermented with LP followed by PP and LC. Significantly (P>0.01) lower pH, water activity, TBARS values and cooking yield were observed in sausages fermented with LC, LP and PP than control. Among treatments significantly (P>0.01) lower pH, water activity, TBARS values and cooking yield were observed in mutton sausages fermented with LP than PP and LC. There was significant (P>0.01) decrease in pH and cooking yield, non-significant decrease in water activity and significant (P>0.01) increase in TBARS values in semi-dry fermented mutton sausages during storage at ambient temperature.There was higher (P>0.01) total plate count, yeast and mould count, coli form count and salmonella count were noticed in control than sausages treated with LC, LP and PP at ambient storage. Among the treatments significantly (P>0.01) higher total plate count, Yeast and Mould count and lower (P>0.01) Salmonella and Coliform count were observed in sausages fermented with LP followed by PP and LC. There was a significant (P>0.01) increase in total plate count and yeast and mould count where as Coliform and Salmonella counts were decreased during storage at ambient temperature in semi-dry fermented mutton sausages. With regards to the organoleptic characteristics significantly (P>0.01) higher colour, flavour and overall acceptability and lower juiciness and tenderness were noticed in sausages fermented with LC, LP and PP than control at ambient storage. Among treatments significantly higher colour and overall acceptability scores and lower juiciness and tenderness scores were noticed in sausages fermented with LP followed by PP and LC. But no significant differences in flavour was noticed in mutton sausages fermented with LC, LP and PP at room temperature. There was a significant (P>0.01) decrease in colour, flavour, juiciness, tenderness and overall acceptability scores during storage at ambient temperature in semi-dry fermented mutton sausages.
Keywords: Fermentation; semi-dry sausages; mutton; starter cultures